Preliminary phytochemical and pharmacological studies of Sesbania grandiflora (L.) Pers - Fojas, F.R; Barrientos, C.M; Capal, T.V; Cruzada, S.F; Sison, F.M; Co, Y.C; Chua, N.G; Gavina, T.L (1982)
Analyses of the phytochemical components of Sesbania grandiflora "katuray" showed that it contains plenty of sterols, saponins, and tannins which are responsible for its various pharmacological properties. Its toxic effect could be attributed to saponin and its histamine-like compound or histamine-releasing content.